Herança do número de dias para floração e maturação em quatro mutantes naturais em soja (Glycine max (L.) Merril) - Gilioli, João Luiz; Sediyama, Tuneo; Silva, José Carlos; Silva Reis, Múcio; Lima Thiébaut, José Tarcísio (Revista Ceres, 2025)
The inheritance of time of flowering and maturity was studied in four soybean crosses among early maturity cultivars: ‘Parand’, “São Luiz’, “Viçoja’ and ‘Hardee’, and their own natural mutants for late maturity: Paranagoiana, PR77-10001, “UFV-1’ and IAC74-2736-10. Segregation in the F2 generation showed that the time of flowering for the mutants Paranagoiana, PR77-10001, and IAC74-2736-10 is controlled by a recessive allele.